Relationship of Rewards and Organizational Support towards Job Satisfaction - Nur Syahrina, Ahmad Labib (2018)
Job satisfaction is important to ensure all employees be more productive in helping the organization to achieve success. This study is done to understand the relationship of two factors of job satisfaction (rewards and organizational support) with job satisfaction. This research focused on private sector employees to understand the factors that affected job satisfaction. A manufacturing company in Penang is selected for the study and 170 questionnaires are distributed to the employees in the company. All variables are measured using 13 items drawn from previous researches. This is a quantitative study and simple random sampling is chosen for this research because each employee in the organization has equal probability of being chosen. The findings of this study provide significant and positive relationship between rewards, working conditions and organizational support with job satisfaction of employees in the organization. There are several recommendations made for future research to have better results. The results from this are hoped can provide to other people besides the organization for a better understanding regarding this matter. By having knowledge regarding job satisfaction of individuals, greater success can be produced and ensure a better future.